Making vancomycin a potent broad-spectrum antimicrobial agent using polyaziridine-stabilized gold nanoparticles as a delivery vehicle - Tiwari A.K.; Nikhil A.; Chaurasia A.; Pandey P.C.; Narayan R.J.; Gupta M.K. (My University, 2025)
The rise of antimicrobial drug resistance among microorganisms presents a global challenge to clinicians. Therefore, it is essential to investigate drug delivery systems to combat resistant bacteria and fungi. This study examined the potential and mode of action of vancomycin-conjugated gold nanoparticles (PEI-AuNP@Van) to enhance vancomycin’s biocidal activity against C. tropicalis, C. albicans, E. coli, and P. aeruginosa. Drug conjugation and nanoparticle characterization were assessed using UV-Vis spectroscopy, X-ray diffraction, TEM, ATR-FTIR, and fluorescence spectroscopy. Effective vancomycin conjugation on polyethyleneimine-stabilized gold nanoparticles was achieved via electrostatic interactions or hydrogen bonding between the COO-/OH groups of vancomycin and the NH- groups of polyethyleneimine, yielding nanoparticles with a narrow size distribution and high zeta potential. The high luminescence of the nanoparticles facilitated their detection in microbial cells. PEI-AuNP@Van was internalized in C. albicans and C. tropicalis but showed surface adsorption in E. coli and P. aeruginosa. The in vitro results indicated that the nanodelivery system exhibited superior biocidal activity against the tested strains compared to free vancomycin and unconjugated AuNPs. The mode of action of PEI-AuNP@Van was cell-type-dependent, involving intracellular reactive oxygen species accumulation, cell membrane integrity loss, and apoptosis. The development of antimicrobial nanoformulations using AuNPs and efficient conjugation systems offers a promising approach to address antimicrobial drug resistance. © The Author(s) 2025.